Empowering Rural Economies: The Impact of MSME Development on Welfare in Binjeita Village, Indonesia - Selvina Baba; Syarwani Canon; Sudirman Sudirman; Frahmawati Bumulo; Ardiansyah (Yayasan Pendidikan Sudirman Mandiri, 2025)
This study investigates the influence of Micro, Small, and Medium Enterprise (MSME) development on community welfare in Binjeita Village, North Sulawesi, Indonesia, a rural area with 132 active MSMEs. The research addresses the gap between government support for MSMEs and actual welfare outcomes, aiming to empirically assess whether MSME performance translates into tangible improvements in income, education, and health. Using a quantitative, positivist approach and a simple causal design, data were collected from 33 randomly selected MSME actors. Instruments measuring MSME development and community welfare were validated and found to be highly reliable (Cronbach’s alpha > 0.90). Descriptive and inferential statistics, including simple linear regression, were employed to test the hypothesis. Results indicate that MSME development is rated as